Bajo la esvástica
Continued by: Fascismo (ZK 53403). - German ed.: Hakenkreuz über Deutschland (ZK 16067). - French ed.: Sous la croix gammée (ZK 53399). - Eng. ed.: Germany under the swastika (ZK 53401). - Swedish ed.: Tyskland under hakkorset (ZK 53400).